Efektifitas Sistem Kebebasan dan Pertahanan Bela Negara Dalam Penyelenggaraan Pemilu - Emaeve Nur Berliantari; Irwan Triadi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Elections have become the mainstream of modern countries. Elections are founded on the principle of equality, namely that every citizen has equal rights and position in the government, therefore every citizen actually has the same power to govern. This people's power is the source of legitimacy and legality of state power. Freedom, Security, Justice and Peace in General Elections must be obtained by all Indonesian people in essence. Of course, this cannot be realized if there is no national stability. Elections do not only rely on the state or military, but involve the strength and role of individual citizens, including non-governmental or private organizations. To hold free, safe, fair and peaceful elections in the General Election, space and mechanisms for full participation must be created, where citizens develop democratic mechanisms and have the power to make decisions in accordance with the wishes of the citizens themselves, without any persuasion or intimidation from other parties. party. interested parties, because the idea of democracy being promoted is actually quite simple, namely to protect the rights of citizens in exercising their freedom to express opinions. For this reason, freedom, security, justice and peace in general elections must be maintained by the government and the government must build stability in the country in implementing elections well.